Labile Serum Factor and Its Effect on Arbovirus Neutralization - Chappell, W. A. (1971)
Enhancement of neutralization of Sindbis, Venezuelan equine encephalitis, Eastern equine encephalitis, Western equine encephalitis, and St. Louis encephalitis viruses by labile serum factor (LSF) in human serum and plasma was demonstrated. Human serum and plasma could be diluted 1:8 and 1:16 and still retain some LSF activity. Satisfactory storage temperatures for retention of LSF activity were −20 or −56 C. Repeated freeze-thaw cycles of serum did not alter LSF activity, but the activity was completely eliminated by heating at 56 C for 5 min. LSF of human serum equally enhanced neutralization by Sindbis immune mouse and rabbit sera; these results suggest a lack of species specificity. Rehydrated lyophilized gunea pig complement did not restore LSF activity to heated human plasma. Serum components responsible for LSF activity were not dialyzable. Discovery of fresh serum without LSF activity established the need to pretest all sera used as LSF sources.